Long term outcomes of survivors of diaphragmatic herniorrhaphy in crossbred cows and buffaloes - Kumar, Ashwani; Saini, Narinder Singh; Mohindroo, Jitender; Sangwan, Vandana; Mahajan, Shashi Kant; Raghunath, Mulinti; Singh, Navdeep (The Indian Journal of Animal Sciences, 2012)
Pregnant and lactating bovine animals that survived diaphragmatic herniorrhaphy done under general anesthesia were observed for postoperative complications, fetal survival and recurrence of diaphragmatic hernia during subsequent calving, milk production level in the same and subsequent lactation. Bovines (22 buffaloes and 2 crossbred cows) were divided into group 1 (13 pregnant) and group 2 (11 lactating). All the animals were followed postoperatively for a mean duration of 15.1±2.56 months (till subsequent calving and lactation). In group 1 animals (8 buffaloes and 1 cow), 69.2% calved at full term with healthy calves and produced 94.4% of normal milk yield in subsequent lactation. Four buffaloes had complications like abortion (2), ventral hernia (1) and death (1). Postoperative complications of abortion and death in group 1 animals were not found related to surgery. In group 2, recently parturated animals (8 buffaloes, 1 cow) resumed mean peak milk yield to 37.5% level of the normal in the same lactation. All animals of group 2 came in estrous and conceived. Seven buffaloes and 1cow calved subsequently and produced mean milk yield of 91.25% that of normal. Three buffaloes developed recurrence of diaphragmatic hernia (2) and ventral incisional hernia (1) in group 2. Majority of the surgical wound related problems (hard swelling, abscessation at postxiphoid or flank skin incision) were managed successfully. Our study revealed that after diaphragmatic herniorrhaphy majority of the surviving pregnant and lactating cows and buffaloes were able to achieve their production and reproduction performance without significant surgery-related complications. Pregnant bovine operated for diaphragmatic hernia are not predisposed to recurrence of diaphragmatic hernia during subsequent calving.